Pattern Recognition 4th Mexican Conference, MCPR 2012, Huatulco, Mexico, June 27-30, 2012. Proceedings - Carrasco-Ochoa, Jesús Ariel; Martinez-Trinidad, Jose Francisco; Olvera López, Jose Arturo; Boyer, Kim L. (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2012)
This book constitutes the refereed proceedings of the 4th Mexican Conference on Pattern Recognition, MCPR 2012, held in Huatulco, Mexico, in June 2012. The 31 revised full papers and 3 keynotes presented were carefully reviewed and selected from 64 submissions and are organized in topical sections on image processing; computer vision and image recognition; pattern recognition and neural networks; and document processing and speech recognition.